(untitled) (Journal of the College of Education for Women, 2019)
Academic libraries characterized from other libraries in the groups of literacy acquired, andways to retrieve this information, where it is supposed supply of various combinations of traditionalsources, electronic information, such as books and references, maps and indexes, CD-ROMs andservice-line and so on, via electronic mediator or via the Internet instead of the mediator paper. Thedigital technology has changed the way you work by academic libraries, where confined to theprimary mission of these libraries to provide prompt services to the needs of researchers, professorsand students, and the provision of reading different materials, including electronic sources thatsupport the curriculum and research in electronic form.Technology changed all functions of the academic library and research, which enabled theresearcher access to the literature, the professional needs or the full text of journal articles from hishome or office through the computer . One study has shown that the provision of such servicesdepends on the provision of systems, modern communications, and provide network infrastructure,and connectivity to databases and information technology and multimedia, but academic libraries inmany countries still lack the provision of basic infrastructure for electronic information.Many academic libraries have been involved in the projects of digital libraries, and the role oflibraries in the digital world is not only providing information and provide a place for storage in abuilding, but to exceed their role more, such as locating method of high-tech to retrieve thatinformation quickly and easily, by creating a portal and electronic outlets that available to thepioneers of the possibility of using this technology for the delivery of services to the beneficiaryremote access electronically.Library Project means establishing electronic links and e-points leading beneficiaries of theelectronic sources available on the Internet by providing a mechanism for search and retrieval. If alibrarians desired to play an active role in this field, they must be to realize these digitaldevelopments and learning them, and bring them to the library for the purpose of providing entrypoints for information.